Qualitative and quantitative analysis of the major constituents in Chinese medicinal preparation Guan-Xin-Ning injection by HPLC–DAD–ESI-MSⁿ - Ruan, Ming; Li, Yi; Li, Xin; Luo, Jianguang; Kong, Lingyi (Journal of pharmaceutical and biomedical analysis, 2012)
Guan-Xin-Ning (GXN) injection, a traditional Chinese medicinal preparation consisting of Radix Salvia miltiorrhiza and Rhizoma Ligusticum chuanxiong, has been used to treat coronary heart disease and angina pectoris in China for decades. In this paper, a HPLC/DAD/ESI-MSⁿ method was successfully developed for qualitative and quantitative analysis of the active components in GXN injection for the first time. 28 compounds were identified by comparison of their retention times and MS spectra (HPLC/DAD/ESI-MSⁿ) with those elucidated standards or recorded literature. 19 of them (danshensu, furoic acid, 3-O-caffeoylquinic acid, protocatechuic aldehyde, p-hydroxybenzoic acid, chlorogenic acid, caffeic acid, 4-O-caffeoylquinic acid, vanillin, 1,3-dicaffeoylquinic acid, 4-hydroxycinnamic acid, ferulic acid, senkyunolide I, senkyunolide H, isosalvianolic acid A, rosmarinic acid, salvianolic acid B, salvianolic acid A and isosalvianolic acid C) were simultaneously determined by HPLC–DAD quantitatively. The analytical method was validated and successfully applied for simultaneous determination of major components in GXN injections from seven different production batches, indicating that the proposed approach was applicable for the routine analysis and quality control of GXN injection.